ANALISIS KASUS PEMBATALAN MEREK PATTA DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS. (STUDI KASUS PUTUSAN PENGADILAN NIAGA NOMOR 13/PDT-SUS-MEREK/2019/PN.NIAGA.JKT.PST) - Renaldi Vietiamawan; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2021)
Mark registration is very important, considering that the right to a mark as an exclusive right for the owner of a mark arises from the existence of registration. In practice, it turns out that a trademark that has been registered can be re-registered. The problems faced in writing this thesis are what is the method of trademark registration in Indonesia and the legal consequences if there is a double registration based on law number 20 of 2016 concerning Geografis Marks and Indications, how is the application of article 21 paragraph (1) letter (a) of Law no. 20 of 2016 related to the cancellation of the mark in the case NO. 13 / PDT, SUS-Mark / 2019 / PN. NIAGA. JKT, PST in the Decision of the Central Jakarta Commercial Court Number 13 / Pdt.Sus-Mark / 2019 / PN. Niaga. Jkt. PST. The research method used in writing this thesis is normative legal research. The results showed that the trademark registration method in Indonesia is constitutive, which means that trademark registration is an obligation to obtain the right to a trademark, because the right to a mark is given to the person or legal entity who registers the mark for the first time and obtains legal protection. On the other hand, the legal consequences can be punished with imprisonment of up to 5 (five) years and / or a maximum fine of Rp. 2,000,000,000.00 (two billion rupiah).